The case of corruption in Covid-19 pandemic in Asia Pacific: Study case of Indonesia - Darynaufal Mulyaman; Achmad Ismail; Ardhi Arsala Rahmani; Angel Damayanti (Journal of Social Studies (JSS), 2023)
The Covid-19 Pandemic is not halting the corruption cases in Asia Pacific; some countries such as North Korea, Malaysia, Thailand, the Philippines, and even China. Nevertheless, Indonesia also suffers from Covid-19 corruption scandals. Corruption cases like social aid corruption by the ex-Social Minister, Juliari Batubara, and vaccines fund corruption by North Sumatera Provincial Health Office authorities are two prominent examples of corruption cases amid the pandemic. Through these cases, such questions as ‘why does corruption in Indonesia still exist even in the Covid-19 pandemic?’ arise. Such cases as the mentioned examples prove that social justice establishment is a concern in Indonesia while the global good governance campaign is not stopping even in pandemics. We argue that such corruption cases affect the Indonesian government to give social justice and lose its responsibility sense to the citizen through a global good governance perspective.